Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/bcp.12360
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and assessment of statin‐related muscular adverse effects

Abstract: Statin-associated muscular adverse effects cover a wide range of symptoms, including asymptomatic increase of creatine kinase serum activity and life-threatening rhabdomyolysis. Different underlying pathomechanisms have been proposed. However, a unifying concept of the pathogenesis of statin-related muscular adverse effects has not emerged so far. In this review, we attempt to categorize these mechanisms along three levels. Firstly, among pharmacokinetic factors, it has been shown for some statins that inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
71
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 105 publications
0
71
0
4
Order By: Relevance
“…23 Moßhammer et al reported that it is not clear whether MCT4-mediated transport of statins across membranes of myocytes plays a role in myopathy. 24 We found that statin-induced cytotoxicity was associated with intracellular accumulation of statins. 17 We hypothesized that suppression of statin-induced cytotoxicity by MCT4 knockdown is associated with intracellular accumulation of statins.…”
Section: Discussionmentioning
confidence: 86%
“…23 Moßhammer et al reported that it is not clear whether MCT4-mediated transport of statins across membranes of myocytes plays a role in myopathy. 24 We found that statin-induced cytotoxicity was associated with intracellular accumulation of statins. 17 We hypothesized that suppression of statin-induced cytotoxicity by MCT4 knockdown is associated with intracellular accumulation of statins.…”
Section: Discussionmentioning
confidence: 86%
“…1 The risk factors for statin-induced myopathy include higher age, female gender, viral infection, genetics, co-morbidities (diabetes, renal failure, liver disease), multiple medications, perioperative period, and concomitant therapy with certain medications. [1][2][3] Patients with genetic variants of CYP3A4 or on concomitant medications that inhibit activity of this enzyme may result in higher statin levels and thus have higher risk of statin-induced myopathy. These medications include azole antifungals, cyclosporine, clarithromycin, other lipid lowering agents, protease inhibitors, calcium channel blockers, and amiodarone.…”
mentioning
confidence: 99%
“…These medications include azole antifungals, cyclosporine, clarithromycin, other lipid lowering agents, protease inhibitors, calcium channel blockers, and amiodarone. [1][2][3] Alcohol abuse also predisposes to statin-induced myopathy.…”
mentioning
confidence: 99%
See 2 more Smart Citations